2014
DOI: 10.4314/ahs.v13i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with iron-folic acid (IFA) therapy among pregnant women in an urban area of south India

Abstract: Background: Anaemia is highly prevalent among pregnant women and iron deficiency is the most important cause. Like many other countries, India has policies to give pregnant women iron supplements. Non-compliance is one important challenging factor in combating anaemia. Objective: To estimate the compliance for IFA tablets among pregnant women and to study the social factors influencing it. Methodology: This study included 190 pregnant women seeking ante-natal care in tertiary health centres in the Mangalore ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
43
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 9 publications
(17 reference statements)
16
43
2
1
Order By: Relevance
“…This means there was an improvement in the proportion of women who consistently took the IFAS tablets as recommended. These findings were similar to a coverage of 67% reported in urban Nairobi County [40] in Kenya and 64.7% reported in India [41] respectively. However, the findings were higher than reports on IFAS coverage from low and medium income countries (LMIC) with similar rural settings namely, South Ethiopia (39.2%), Pakistan (38.3%), [38], Nigeria (37.5%) [42] and Western Ethiopia (20.4%) [20].…”
Section: Discussionsupporting
confidence: 90%
“…This means there was an improvement in the proportion of women who consistently took the IFAS tablets as recommended. These findings were similar to a coverage of 67% reported in urban Nairobi County [40] in Kenya and 64.7% reported in India [41] respectively. However, the findings were higher than reports on IFAS coverage from low and medium income countries (LMIC) with similar rural settings namely, South Ethiopia (39.2%), Pakistan (38.3%), [38], Nigeria (37.5%) [42] and Western Ethiopia (20.4%) [20].…”
Section: Discussionsupporting
confidence: 90%
“…This low proportion has also been found in several developing countries such as Cambodia, Mali, Nepal and Indonesia, where they are respectively 47%, 28%, 20.7% and 40% [17] [18] [19] [20]. However, relatively high rates have also been observed in other developing countries such as Nigeria [21] and India [22] where the authors reported rates of 65.9% and 64.7%, respectively. In Europe, studies of pregnant English women indicated that 70% of these women adhered to iron supplementation [23] [24].…”
Section: Discussionmentioning
confidence: 86%
“…As per the recommendation of WHO (DeMaeyer, 1989), amount of iron absorption is influenced by the combination of foods taken in a given meal. Studies by Galloway and McGuire(1994), Hallberg et al, (1966), Beard (2000), Mithra et al, (2013) have argued that common reasons for not consuming IFA tablets are side effects, lack of access, misunderstood instructions etc. Consumption of IFA tablets is mostly influenced by age, socioeconomic status, community awareness regarding importance of IFA tablets.…”
Section: Iron Bioavailability: Notes From the Fieldmentioning
confidence: 99%